MLH1 Deficiency Down-Regulates TLR4 Expression in Sporadic Colorectal Cancer - Scarpa, Melania; Ruffolo, Cesare; Kotsafti, Andromachi; Canal, Fabio; Erroi, Francesca; Basato, Silvia; Dall’Agnese, Lucia; Fiorot, Alain; Pozza, Anna; Brun, Paola; Bassi, Nicolò; Dei Tos, Angelo; et al. (Frontiers in Molecular Biosciences, 2021)
Patients with mismatch repair (MMR)-deficient colorectal cancer (CRC) have a more favourable prognosis than patients with tumours with intact MMR. In order to obtain further insights on the reasons for this different outcome, we investigated the interplay between MMR genes and TLR4/MyD88 signalling. The cancer genome atlas (TCGA) databases were selected to predict the differential expression of TLR4 in colon cancer and its correlation with MMR genes. Moreover, the expression of MMR genes and TLR4 was evaluated by immunohistochemistry in 113 CRC samples and a cohort of 63 patients was used to assess TLR4 mRNA expression and MLH1 epigenetic silencing status. In vitro, the effect of MLH1 knockdown on TLR4 expression was quantified by Real Time PCR. TLR4 expression resulted dependent on MMR status and directly correlated to MLH1 expression. In vitro, MLH1 silencing decreased TLR4 expression. These observations may reflect the better prognosis and the chemoresistence of patients with CRC and MMR defects.